Identifying Effective Approaches for Dissemination of Clinical Evidence – Correlation Analyses on Promotional Activities and Usage of a Guideline-Driven Interactive Case Simulation Tool in a Statewide HIV-HCV-STD Clinical Education Program - Wang, Dongwen (Stud Health Technol Inform, 2015)
Dissemination of the latest clinical evidence to community-based healthcare providers is a critical step to translate biomedical knowledge into clinical practice. We performed a study to analyze the correlations between the promotional activities and the usage of a guideline-driven interactive case simulation tool (ICST) for insomnia screening and treatment in a statewide HIV-HCV-STD clinical education program. For this purpose, we tracked users’ interactions with the ICST and the sending of promotional email newsletters during a study period of 44 weeks. Results showed that promotional activities were strongly correlated with the number of audience as well as the intensity of use of the target resource. The strength of correlation varied in specific use contexts. Strong correlations were found between the sending of email newsletters and the intensity of resource use by promotion recipients, by new users, and through the most convenient access channel associated with the promotion. Selection of approaches for resource dissemination should consider the potentials and limitations of use contexts to make them more effective.